Function of Germline-specific Ribonucleoprotein granules-from germline to cancer - Olotu, Opeyemi (fi=Turun yliopisto|en=University of Turku|, 2023)
Male germ cells undergo complex differentiation from embryonic germ cells, through postnatal spermatogenesis to highly specialized spermatozoa. Precise regulation of gene expression is critical for meiosis and morphological changes in differentiating male germ cells. Large ribonucleoprotein (RNP) granules and germ granules, appear in the cytoplasm of germ cells to support the high requirement for posttranscriptional gene regulation. In this study, we elucidated the functions of two types of germ granules, the intermitochondrial cement (IMC) and chromatoid body (CB). We studied the protein composition of the IMC and verified its central role in the production of PIWI-interacting RNAs (piRNAs). We also identified two new IMC components, EXD1 and EXD2, and characterized their association with germ granules and the piRNA biogenesis machinery. In addition, we characterized the collaboration between EXD1 and the Tudor domain-containing protein TDRD12 in piRNA biogenesis in embryogenic testis and also revealed the essential role of this collaboration in male fertility. We further demonstrated that the functions associated with germ granules are utilized in cancer cells, as the germ granule protein DDX4 forms cytoplasmic granules in many tumor types. These DDX4 complexes contained various RNA-binding proteins, including splicing regulators and known germ granule proteins. Deletion of DDX4 in cancer cells led to transcriptome imbalance and impaired splicing landscape of genes that contribute to cancer growth and invasiveness, and consequently delayed tumor growth. Moreover, the presence of DDX4 granules in human cancer samples was shown to correlate with a poor prognosis for the patient. The results of this study highlight the importance of germ granules in the piRNA pathway during spermatogenesis and provide evidence for the novel role of germ granule components in transcriptome control in cancer cells that promote malignant properties.